2017
DOI: 10.1088/1538-3873/aa7112
|View full text |Cite
|
Sign up to set email alerts
|

The Astrophysics of Visible-light Orbital Phase Curves in the Space Age

Abstract: The field of visible-light continuous time series photometry is now at its golden age, manifested by the continuum of past (CoRoT, Kepler), present (K2), and future (TESS, PLATO) space-based surveys delivering high precision data with a long baseline for a large number of stars. The availability of the high quality data has enabled astrophysical studies not possible before, including for example detailed asteroseismic investigations and the study of the exoplanet census including small planets. This has also a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 207 publications
(390 reference statements)
1
107
0
Order By: Relevance
“…The presence of inhomogeneous clouds is thus likely common because all of the planets with robust two dimensional atmospheric information have signatures of inhomogeneous clouds (Shporer & Hu 2015). In observations of optical phase curves, however, there can be substantial non-atmospheric processes, such as doppler boosting, tidal ellipsoidal distortion, and planetary obliquity, that require approximations for this form of analysis (see review by Shporer 2017). This, coupled with the comparative difficulty of phase curve observations (Shporer 2017;Parmentier & Crossfield 2018) makes this method of probing inhomogeneous cloud cover difficult to generalize to the vast majority of hot Jupiters.…”
Section: Finding a Transmission Signature Of Inhomogenous Cloud Covermentioning
confidence: 99%
“…The presence of inhomogeneous clouds is thus likely common because all of the planets with robust two dimensional atmospheric information have signatures of inhomogeneous clouds (Shporer & Hu 2015). In observations of optical phase curves, however, there can be substantial non-atmospheric processes, such as doppler boosting, tidal ellipsoidal distortion, and planetary obliquity, that require approximations for this form of analysis (see review by Shporer 2017). This, coupled with the comparative difficulty of phase curve observations (Shporer 2017;Parmentier & Crossfield 2018) makes this method of probing inhomogeneous cloud cover difficult to generalize to the vast majority of hot Jupiters.…”
Section: Finding a Transmission Signature Of Inhomogenous Cloud Covermentioning
confidence: 99%
“…To highlight a few examples, Barclay et al (2013) found evidence for a Moon-size terrestrial planet in a 13.3-day period orbit, Quintana et al (2014) found evidence of an Earth-size exoplanet in the habitable zone of the M dwarf Kepler-186, and Jenkins et al (2015) statistically validated a super-Earth in the habitable zone of a G-dwarf star. Additionally, for several massive planets Kepler data have enabled measurements of planetary mass and atmospheric properties by using the photometric variability along the entire orbit (Shporer et al 2011;Mazeh et al 2012;Shporer 2017). Kepler data have also revealed hundreds of compact, co-planar, multiplanet systems, e.g., the six planets around Kepler-11 (Lissauer et al 2011a), which collectively have told us a great deal about the architecture of planetary systems (Lissauer et al 2011b;Fabrycky et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the most massive planets, the periodic blue-and red-shifting of the host star's spectrum and the tidal bulge raised on the star's surface can yield additional phase curve terms that are detectable in longbaseline photometry. These contributions to the total observed photometric modulation are referred to as Doppler boosting and ellipsoidal distortion; see Shporer (2017) for a review of these processes.…”
Section: Introductionmentioning
confidence: 99%